State Editors luncheon, Alaska Yukon Pacific Exposition, Seattle, July 1909. - Nowell, Frank H., 1864-1950 (1909)
State editors, guests of the Seattle Press Club for Washington Press Day, July 1909. On verso of image: State Editors To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number